PROSEDUR HUKUM DAN PERTIMBANGAN ETIS DALAM PERMOHONAN IZIN POLIGAMI DI PENGADILAN AGAMA INDONESIA - Lubis, Nanang Ardiansyah; Syahmedi, Ramadhan (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study aims to explore and describe the judicial system in Indonesia, particularly the Islamic judicial system, as well as explain the legal process in terms of polygamy license applications in Indonesian Religious Courts. Analyze the ethical considerations that should be taken into account in applying for and deciding on a polygamy permit application. This research uses a qualitative approach with descriptive analysis. Data were collected from Islamic law literature, Law Number 1 of 1974 on Marriage, Compilation of Islamic Law (KHI), and Government Regulation Number 9 of 1975. The process of applying for a polygamy license involves several stages, including the submission of the application, summoning of the trial, examination and consideration, determination of the verdict, as well as the possibility of appealing the verdict. Ethical considerations in a polygamy license application emphasize the importance of justice, both financial and emotional, for the wife and children. The Qur'an and Hadith emphasize the importance of justice in polygamy. By carefully following these legal procedures and ethical considerations, it is hoped that the decision made by the Religious Court will reflect justice and the interests of all parties involved